Results of the implantation of bone-anchored hearing aids in patients with treacher-collins syndrome - Oliveira,Alexandra Kolontai de Sousa (2013)
INTRODUCTION: Treacher-Collins syndrome is characterized by craniofacial malformations, narrowing of the external auditory canal (EAC), and, in 30% of cases, agenesis of the canal and ossicular chain defects. The use of hearing aids (HA) is not possible in cases in which agenesis or stenosis of the EAC accompanies conductive deafness. In contrast, bone conduction implants such as the Bone Anchored Hearing Aid (BAHA®) allow direct stimulation of the cochlea and are thus superior to conventional hearing aids in cases of severe conductive hearing loss. OBJECTIVE: To present 2 cases of patients with Treacher-Collins syndrome who underwent implantation of BAHA®. CASES REPORTS: The first patient was a 52-year-old woman diagnosed with Treacher-Collins syndrome who presented with severe bilateral mixed hearing loss and a history of unsuccessful previous use of a bone contact conduction device. The BAHA® implantation was uneventful, and the post-operative results were good. The second patient was a 14-year-old girl who was also diagnosed with Treacher-Collins Syndrome with bilateral moderate conductive hearing loss by audiometry. The use of a bone vibrator contact device did not improve her hearing; however, implantation of a BAHA® resulted in a decreased gap postoperatively. FINAL COMMENTS: BAHA® hearing devices provide adequate rehabilitation and consequent improvement of the quality of life in patients with Treacher-Collins syndrome.